The relationship between common ability to perform the ballistic stretch-shortening cycle movement in unilateral horizontal jump events and performance of various jump events - Fujibayashi, N.; Kariyama, Y.; Kinomura, Y.; Zushi, K. (Japan Journal of Physical Education, Health and Sport Sciences, 2013)
The purpose of this study was to develop a new method for measuring the common ability to perform the ballistic stretch-shortening cycle movement in unilateral horizontal jump events and to investigate the relationship between the performances of various jump events. Ten male college track and field athletes performed the rebound long jump test (RLJ test). The participants jumped from a 0.1-m-high step to the ground after an approach run (falling jump), followed by jumping without interruption for as far as possible (propulsive jump). The falling jump distance was set at 1, 2, or 3 m, and touchdown velocity, jumping distance, contact time, ground reaction force and leg joint torque were measured for all three falling jump distances. To evaluate RLJ test performance, the RLJ index was calculated by dividing jumping distance by contact time. Simultaneously, the rebound jump test (RJ test) method for measuring the common ability to perform the ballistic stretch-shortening cycle movement in lateral vertical jump events and the five steps of bounding (5SB) method for measuring the common ability to perform unilateral horizontal jump events were conducted. We found that there were no significant correlations between the jumping height, contact time, and RJ power [RJ power (W/kg)=jumping height (m)/(contact time (sec)/2)] of the RJ test and the jumping distance, contact time, and RLJ index of the RLJ test, or any of the three falling jump distances. Thus, it was concluded that abilities to perform those two tests differed. On the other hand, there was a strong correlation (r=0.859) between the RLJ index measured for a falling jump distance of 3 m (RLJ index3) and the IAAF score of track and field athletes. In addition, the pattern and magnitude for the ground reaction force and leg joint torque measured during the RLJ for a falling jump distance of 3 m had similar characteristics to takeoff in the long jump or triple jump during a competition. Furthermore, 5SB was correlated (r=0.790) with the IAAF score, but the correlation coefficient was less than that of the RLJ index3. The RJ index was not correlated with the IAAF score. These results demonstrate the significance of using the RLJ test and RLJ index from a 0.1-m-high step for measuring the common ability to perform the ballistic stretch-shortening cycle movement in unilateral horizontal jump events.